2021
DOI: 10.1007/978-3-030-77688-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Helping Kids! Cross-Cultural Research on Children’s Prosocial Behavior in Societies Transitioning to Peace

Abstract: Intrastate conflicts dominate the twenty-first century. Understanding the psychological mechanisms necessary to transform such settings into more peaceful societies is essential. Toward that end, Helping Kids! is a cross-cultural project that focuses on children in conflict-affected contexts. Moving away from the conceptualization of youth as perpetrators or powerless victims, Helping Kids! recognizes that children can foster a peaceful future, despite growing up in the shadow of war. This chapter approaches p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Yet the findings also point to children’s peace-building potential. In each postaccord setting, children demonstrated a willingness to share resources with a member of a conflict-rival outgroup (Bähr et al, in press). As outlined by the DPM, children’s outgroup prosocial behavior in the microsystem, such as sharing with an individual member of the conflict-rival group (Taylor, O’Driscoll, et al, 2020), may have implications for prosociality in adolescence and emerging adulthood that aims to promote constructive change in the exo- and macrosystems (Taylor et al, 2018; Taylor & McKeown, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yet the findings also point to children’s peace-building potential. In each postaccord setting, children demonstrated a willingness to share resources with a member of a conflict-rival outgroup (Bähr et al, in press). As outlined by the DPM, children’s outgroup prosocial behavior in the microsystem, such as sharing with an individual member of the conflict-rival group (Taylor, O’Driscoll, et al, 2020), may have implications for prosociality in adolescence and emerging adulthood that aims to promote constructive change in the exo- and macrosystems (Taylor et al, 2018; Taylor & McKeown, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood cohesion also has positively and directly affected prosocial behavior in Italy (Lenzi et al, 2012). Finally, comparing predictors of children’s prosocial behaviors across different macrosystems through cross‐national research is an essential piece of this puzzle, but is still lacking (for exceptions, see Carlo, Koller, Eisenberg, Da Silva, & Frohlich, 1996, comparing the United States and Brazil; Bähr et al, in press, comparing Northern Ireland, Croatia, Kosovo, the Republic of Macedonia, and Israel). For the most part, studies about broader influences on children’s prosocial behavior are rare.…”
Section: Directions For Process‐oriented Researchmentioning
confidence: 99%
“…In collectivism, individuals are expected to assist members within their social networks. It has been observed that, in comparison to individualist societies, collectivist societies tend to view extending social help towards others as a priority (Bahr et al., 2021 ). This research is also compatible with the theory of planned behavior.…”
Section: Discussionmentioning
confidence: 99%